Perencanaan mewujudkan profil pelajar pancasila di SMA Negeri 1 Payaraman - Yanuarini, Dwi; Harapan, Edi; Rahman, Andi (Media Manajemen Pendidikan, 2024)
This research aims to obtain a clear picture at the planning stage of strengthening the Pancasila student profile project in realizing the Pancasila student profile at SMA Negeri 1 Payaraman. This research was conducted in the first year of implementation of the Independent Change Level 2 Independent Curriculum in class X for the 2022/2023 academic year. This research method uses a qualitative case study approach. The informants in this study consisted of the principal, deputy principal, teachers, students, committee members and parents. The data collection techniques used in this research are observation, interviews and documentation. The data validity technique in this research was carried out using triangulation, then the data was analyzed using the Miles and Huberman model by collecting data, reducing data, presenting data, and drawing conclusions. The results of this research show that the supporting documents have been fulfilled and are supported by the teacher's understanding regarding P5 planning. So it can be concluded that the P5 planning stage at SMA Negeri 1 Payaraman was good with the implementation of 6 of the 8 planning stages including data and information collection, analysis and diagnosis, policy formulation, target setting, budgeting and plan implementation.